2008
DOI: 10.1002/pola.22543
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of micelles formed by amphiphilic star block copolymers prepared in the presence of a nonmetallic monomer activator

Abstract: In this article, we describe the synthesis of PEG‐b‐polyester star block copolymers via ring‐opening polymerization (ROP) of ester monomers initiated at the hydroxyl end group of the core poly(ethylene glycol) (PEG) using HCl Et2O as a monomer activator. The ROP of ε‐caprolactone (CL), trimethylene carbonate (TMC), or 1,4‐dioxan‐2‐one (DO) was performed to synthesize PEG‐b‐polyester star block copolymers with one, two, four, and eight arms. The PEG‐b‐polyester star block copolymers were obtained in quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…CMC is an important parameter to evaluate the stability of micelles as drug delivery carriers. The lower the CMC is, the stronger the anti‐dilution ability of micelles is in body fluid . In order to measure the CMC of SAPU, the intensity ratio of the peak at 337.0 nm to the peak at 334.5 nm ( I 337.0 / I 334.5 ) from excitation spectra was plotted against the logarithm of micelle concentration (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CMC is an important parameter to evaluate the stability of micelles as drug delivery carriers. The lower the CMC is, the stronger the anti‐dilution ability of micelles is in body fluid . In order to measure the CMC of SAPU, the intensity ratio of the peak at 337.0 nm to the peak at 334.5 nm ( I 337.0 / I 334.5 ) from excitation spectra was plotted against the logarithm of micelle concentration (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, many reports have mainly focused on researching linear amphiphilic polyurethane micelles as delivery vehicles of drugs and genes . Generally, linear amphiphilic copolymers have a larger critical micelle concentration (CMC) and micelles are formed only through physical interaction, which are not beneficial to maintaining micellar stability . Because the micellar structure will be easily disrupted and the burst release of entrapped drugs will happen after intravenous injection into the bloodstream, the bioavailability of drugs will be reduced and the large drug concentration fluctuation will produce toxic side effects to healthy tissue .…”
Section: Introductionmentioning
confidence: 99%
“…This is in accordance with the general observation that crystallization of individual blocks in star shaped copolymer micelles is hampered, resulting in shifting of the endothermic curve. 36,37 The SABPEI 5050 combination was found to be more crystalline, indicating the ability of folded SA moieties in complete crystallization. Earlier studies on star shaped micelles revealed that micellization ability is directly proportional to crystallinity.…”
Section: Physical Characterization Of Lipopolymermentioning
confidence: 97%
“…Recently, micellization of block copolymers with a complex architecture was investigated 11, 12. Typically, star‐shaped (AB n ‐type) block copolymers exhibit fundamentally different micellization behavior when compared with the corresponding linear counterparts 13. Their micellization is less favorable with a considerably lower association number.…”
Section: Introductionmentioning
confidence: 99%